Ultrasound-Guided Liver Surgery An Atlas - Torzilli, Guido; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2014)
Ultrasound guidance of liver surgery is a very sophisticated approach that permits the performance of otherwise unfeasible operations, discloses the true extent of tumors, increases the indications for hepatectomy, and renders surgery safer. Despite this, it has remained relatively neglected in the literature over the past two decades, during which time much progress has been achieved. This is the first atlas on the subject, and it is comprehensive in scope. The state of the art in the use of ultrasound for resection guidance is carefully documented, and new techniques for exploration of the biliary tract and facilitation of transplant surgery are presented. Further important topics include the role of ultrasound in laparoscopic approaches, the use of contrast agents for diagnosis and staging, and developments in the planning of surgical strategy. The editor is a leading authority whose group has been responsible for a variety of advances in the field. He has brought together other experts whose aim throughout is to provide clear information and guidance on the optimal use of ultrasound when performing liver surgery. This atlas is intended especially for hepatobiliary surgeons but will also be of considerable value for general surgeons.
Part I Introductory aspects: 1 Technological requirements for ultrasound-guided liver surgery -- 2 Technical tricks to start exploring the liver with ultrasound -- 3 Exploring the liver with ultrasound following its anatomical features -- Part II Diagnosis and Staging: 4 Diagnosis and staging: intraoperative ultrasound -- 5 Diagnosis and staging: contrast enhanced intraoperative ultrasound and intravascular contrast agents -- 6 Contrast-enhanced intraoperative ultrasound using liver-specific contrast agents -- Part III Hepatobiliary Surgery: 7 Planning of the surgical strategy -- 8 Resection guidance -- 9 Intraoperative cholangio-ultrasound in the study of the biliary tree -- Part IV Liver Transplantation: 10 Liver transplantation from deceased donors -- 11 Liver transplantation from living donors -- Part V Minimally Invasive Surgery and Interventional Procedures: 12 Laparoscopic ultrasonography: impact in liver surgery -- 13 Ultrasound-guided intraoperative ablation therapies -- 14 Robotic ultrasound-guided liver resections -- 15 Conclusions: future perspectives for the use of ultrasound in liver surgery.
Keywords: Medicine; Diagnosis, Ultrasonic; Abdomen -- Surgery; Medicine & Public Health; Abdominal Surgery; Ultrasound; Medicine/Public Health, general